2020
DOI: 10.3389/fpsyt.2020.574143
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Status Among Anesthesiologists and Operating Room Nurses During the Outbreak Period of COVID-19 in Wuhan, China

Abstract: Background: Coronavirus Disease 2019 (COVID-19) caused by a novel strain of coronavirus (SARS-CoV-2) posed a major threat to public health. Anesthesiologists and operating room (OR) nurses are at high risk of occupational exposure to SARS-CoV-2 and developing COVID-19. We conducted a single-center survey to investigate the psychological status and perceived social support among operation room (OR) medical staffs during the outbreak of Coronavirus Disease 2019 (COVID-19).Methods: A total of 197 OR medical staff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…Those findings were not in agreement with the findings published from Italy by Di Tella et al [ 42 ], explaining that frontline HCW are in a daily struggle to keep the COVID-19 patients alive, have insufficient rest, are under a permanent threat of being infected, and are isolated from family due to their workload putting them at higher risk for depression. Our findings were contrary to the findings from Wuhan by Li et al [ 43 ], who reported that anesthesiologists and nurses exposed to COVID-19 patients were more vulnerable to experience depression and anxiety. This study was performed during the period of Wuhan lockdown during the first COVID-19 wave before the availability of any vaccine and when little information was known about the virus.…”
Section: Discussioncontrasting
confidence: 99%
“…Those findings were not in agreement with the findings published from Italy by Di Tella et al [ 42 ], explaining that frontline HCW are in a daily struggle to keep the COVID-19 patients alive, have insufficient rest, are under a permanent threat of being infected, and are isolated from family due to their workload putting them at higher risk for depression. Our findings were contrary to the findings from Wuhan by Li et al [ 43 ], who reported that anesthesiologists and nurses exposed to COVID-19 patients were more vulnerable to experience depression and anxiety. This study was performed during the period of Wuhan lockdown during the first COVID-19 wave before the availability of any vaccine and when little information was known about the virus.…”
Section: Discussioncontrasting
confidence: 99%
“…Support from parents and peers appear to be a very important aspect of social support that the students had embraced, and it plays significant roles in students’ socialization, behavioral development, and mental health [ 8 ]. It has been previously observed that higher social support is associated with fewer depressive symptoms [ 14 , 15 ], and well received social support can limit the prevalence of adolescents’ online addiction [ 16 ]. As a result, social support may attenuate the relationship between depressive symptoms and IGD in college students.…”
Section: Introductionmentioning
confidence: 99%
“…The total score ranged from 12 to 84 with higher indicating higher level of social support. The Chinese version of MSPSS exhibited good reliability and validity ( Li et al., 2020 , 2021b ; Yang et al., 2020 ). In this survey, Cronbach's α coefficient of internal consistency of this scale was 0.949.…”
Section: Methodsmentioning
confidence: 97%